An Oligocene giant rhino provides insights into Paraceratherium evolution - Tao Deng (Nature Portfolio, 2021)
Deng et al. report a new species of giant rhino, Paraceratherium linxiaense, from specimens of the upper Oligocene Jiaozigou Formation in China with an age of 26.5 Ma. Morphological analysis of the completely preserved skull with articulated mandible and atlas reveals a high level of specialization and the formation of a clade with P. lepidum with close ties to P. bugtiense.